Market concepts and their effect on Lithuania's economic reforms - Dalia Vidickienė (Politologija)
This article gives favorable analysis of various market concepts common in scientific literature, as well as their effect upon the strategy of economic reform in Lithuania. The author promises to complement the market description, a composite part of classic economic theory, which selects only one of its parameters, with market conceptions as provided by other economic theories and, eventually, describe the market as a three-dimensional object-subject-subjective system. Such a point of view, save resting on a synergetic principle, sets pace for mutual co-ordination of, at first hand, contradictory concepts of the market reflecting its different evolutionary stages. Proposals concerning the role of government institutions in the formation of each of the three market parameters to be selected are put forward. The author states that alongside with the market reforms coming in the former socialist countries, classic economic theory cannot provide for a satisfying answer to the question "What is the market?". Furthermore, despite the fact that market researches are treated to be among the core tasks of modern science, in scientific literature it is extremely difficult to find the description of what the market is.